KEBIJAKAN PEMBINAAN ATLET OLEH DINAS PEMUDA DAN OLAHRAGA (DISPORA) KOTA TANJUNGPINANG - Bintana, Muhammad Riau (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2017)
Coaching is done by the Department of Youth and Sports of Tanjungpinang done only whenthe event will be held, there is no long-term development programmed, planned and sustainableperformed. Planning the future development of the athletes who have not been there and facilities thatdo not support in fostering where many are not national standards even hire private parties. Theresearch problems are how policies coaching athletes by the Department of Youth and Sports (Dispora)TanjungpinangThe purpose of this study was to determine the Athlete Development Policy by theDepartment of Youth and Sports (Dispora) Tanjungpinang. Basic research that relies on theoreticalconcepts M. Furqan (2002: 3) on sports coaching achievements usually follow the stages ofdevelopment that are based on the theory of the pyramid. Furthermore, the frameworks continue torefer to the concept of the above theory with each aspect and above indicators. This type of research isdescriptive using qualitative approach, the research informants amounted to 9 with 1 as keyinformants. Data collection techniques using interview techniques using (interview guides),observation, documentation subsequent data analysis with qualitative.The results showed in the training ground for the athletes there is a mismatch of threedimensions above. From some aspects show that the absence of long-term development policy of theathlete. Planning after the athletes who followed the event to still do the coaching has not been done.Coaching standards and targets it is necessary to measure the athletes ability. Facilities andinfrastructure are inadequate and national standards. Should the effort of the Department of Youthand Sport to make a long-term development policies, planning ahead to accommodate athletes whoexcel and build a complete infrastructure and a national standard that coaching is done against anathlete can be done effectively and more leverage.